2003
DOI: 10.1080/10225706.2003.9684104
|View full text |Cite
|
Sign up to set email alerts
|

Strategic or Tactical? Foreign Research and Development in Developing Countries, a Case Study of China

Abstract: This study oflers a new framework of classifying research and development (R&D) at multinational corporations (MNCs): strategic vs. tactical. Strategic R&D facilities are serving not only domestic markets, but also the global markets; they are involved not only in development, but also in original research; they are working not only on short-term projects, but also on projects that are crucial for MNCs' future in the long-term. Mainstream theories have limited possible locations of strategic R&D facilities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The decentralisation of R&D is further enabled and facilitated by advances in telecommunication technologies (Howells, 1990(Howells, , 1995. The few studies on foreign R&D in developing countries (Gassmann and Han, 2004;GEI, 2001;Reddy, 1997;Reddy and Sigurdson, 1997;Sun, 2003;Sun et al, 2006;Wen, 2007a, 2007b;von Zedtwitz, 2004;Walsh, 2003;Xue et al, 2001) have confirmed the findings from the general studies on foreign R&D, and factors from both the demand side and the supply side are important in explaining the recent surge of R&D performed by foreign companies. In the case of China, its growing domestic market and increasing roles as a 'world's factory', as well as its large pool of well-educated labour have become a huge attraction to foreign companies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The decentralisation of R&D is further enabled and facilitated by advances in telecommunication technologies (Howells, 1990(Howells, , 1995. The few studies on foreign R&D in developing countries (Gassmann and Han, 2004;GEI, 2001;Reddy, 1997;Reddy and Sigurdson, 1997;Sun, 2003;Sun et al, 2006;Wen, 2007a, 2007b;von Zedtwitz, 2004;Walsh, 2003;Xue et al, 2001) have confirmed the findings from the general studies on foreign R&D, and factors from both the demand side and the supply side are important in explaining the recent surge of R&D performed by foreign companies. In the case of China, its growing domestic market and increasing roles as a 'world's factory', as well as its large pool of well-educated labour have become a huge attraction to foreign companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite its increasing importance, foreign R&D in developing countries only recently has received some attention (Gassmann and Han, 2004;GEI, 2001;Reddy, 1997;Reddy and Sigurdson, 1997;Sun, 2003;Sun et al, 2006Sun et al, , 2008Wen, 2007a, 2007b;von Zedtwitz, 2004;Walsh, 2007;Xue et al, 2001). This study wishes to contribute to the field of R&D globalisation in general and foreign R&D in China in particular on a few fronts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Y. Sun (2003) indicates an alternative approach based on two different categories: strategic or tactical according to their relevance. Strategic R&D gives more importance and relevance to the MNE global markets and it has a long-term aim.…”
Section: Other Studiesmentioning
confidence: 99%
“…Multinational Enterprises (MNE) are increasingly adopting a global strategy for their activities of research and development (R&D); consequently, academics have shown growing interest in this phenomenon since the 1990s.The most debated areas of interest include the classification of the ac-tivities carried out abroad (Kuemmerle, 1999;Y. Sun, 2003), the choice of the location of R&D centers (Dougherty, Inklaar, McGuckin, & Van Ark, 2003;Belderbos, Lykogianni, & Veugelers, 2008), the organization of R&D networks all around the world (Alfaro & Chen, 2009) and the MNE strategies to run a global R&D process (Arora, Fosfuri, & Gambardella, 2001;Chesbrough, 2003;Ernst, 2005).…”
Section: Introductionmentioning
confidence: 99%